MAKNA SIMBOL PROSESI DALAM RITUAL AMBIL SEMANGAT SUKU TIDUNG - Muhammad Thobroni; nfn Helmiyanto (Madah: Jurnal Bahasa dan Sastra, 2017)
The study aims to describe the meaning of the symbol of the procession of Ritual Ambil Semangat in Sembakung, Nunukan, North Kalimantan. Ambil Semangat (Take Spirit) is a customary ritual to cure diseases caused by spirits. Research data is obtained by recording, note taking, and interview techniques, then the data was collected, identified and classified. The research data in the form of recording and notes about the meaning of the symbol of Ritual Ambil Semangat in Sembakung Nunukan. The study focuses on the meaning of symbols of the Ambil Semangat Procession with a semiotic approach. Research on the meaning of ritual procession symbols Ambil Semangat in Sembakung Nunukan uses semiotic study by applying the theory of triangle of meaning (sign, object, and interperant). The result of the study shows that there are unique meaning in the stages of the process. The order of ritual Ambil Semangat are: Pembukaan, Potong Lilin Tiga Sisi, Mengisi Air dalam Ember, Memulai Ritual Ambil Semangat, Menyalakan Lilin Kuning, Tempel Lilin Kuning, Putar Mangkuk pakan, Usapan air Salawat Nabi, Ambil Syarat Nabi Ilyas As, Pemanggil Roh, Pulang dengan Doa, Pasang Ikat, Hambur Pakan, Masuk Air, Air Nabi Khaidir As, Telan Air Salawat Nabi Khaidir As, Penutup.